2000
DOI: 10.2472/jsms.49.9appendix_221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Charge/Discharge of Li1-xNi1-yMnyO2 on Their Crystal Structures and Electronic States

Abstract: The variations of structure and electrochemical properties of Li1-xNi1-yMnyO2 (y=0 and 0.2) were studied as lithium was deintercalated from the materials. The LiNi1-yMnyO2 was prepared by easily available LiOH, Ni(OH)2 and ƒÁ-MnOOH under air flow. Exchange of nickel into the lithium site (3(a)site) made it difficult for the lithium ion to move through the lithium layer, and decreased the electrical capacity for cyclic charge/discharge. Partial substitution of manganese for nickel was effective in preventing ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…LNMO-3# shows a higher Ni 2P 3/2 binding energy (858.7 eV) than LNMO-3, due to that its precursor NMO-3# is obtained by oxidation treatment of NMO-3 in NaClO solution. Moriga et al have investigated the binding energies of Ni in LiNi 0.8 Mn 0.2 O 2 and LiNiO 2 , and found that Ni 2+ and Ni 3+ in the compounds have binding energies of 853.7 and 855.3 eV, respectively, which are somewhat lower than that in our LNMO samples. This may be due to the low Ni content in our samples.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…LNMO-3# shows a higher Ni 2P 3/2 binding energy (858.7 eV) than LNMO-3, due to that its precursor NMO-3# is obtained by oxidation treatment of NMO-3 in NaClO solution. Moriga et al have investigated the binding energies of Ni in LiNi 0.8 Mn 0.2 O 2 and LiNiO 2 , and found that Ni 2+ and Ni 3+ in the compounds have binding energies of 853.7 and 855.3 eV, respectively, which are somewhat lower than that in our LNMO samples. This may be due to the low Ni content in our samples.…”
Section: Resultscontrasting
confidence: 56%
“…This result can be explained from the characteristic of LNMO structure. On the basis of an assumption that Ni occupies the same site as Mn, , the layered LNMO can be expressed by a general formula as follows where { } and [ ] are octahedral sites in the layer of Li atom and octahedral sites in the layer of Mn atom, respectively, with x ≤ 1, y ≤ 1 / 3 , ( y + n + m ) ≤ 1. Ni and a part of the Li atoms can be located in the Mn site …”
Section: Resultsmentioning
confidence: 99%
“…The most widely known Co‐free cathode, Li[Ni 0.5 Mn 0.5 ]O 2 , has attracted significant interest; however, its relatively low capacity renders the cathode unsuitable for applications requiring high‐energy‐density . To increase the discharge capacity, Li[Ni 0.6 Mn 0.4 ]O 2 , Li[Ni 0.7 Mn 0.3 ]O 2 , Li[Ni 0.8 Mn 0.2 ]O 2 , and Li[Ni 0.9 Mn 0.1 ]O 2 cathodes have been proposed, but their inferior cycling stability make their practical utilization questionable . In this study, we systematically investigate the characteristics of a Co‐free Ni‐rich Li[Ni x Mn 1‐ x ]O 2 cathode by gradually removing Co from Li[Ni 0.9 Co 0.1 ]O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 10–12 ] To overcome the limitations of Li[Ni 0.5 Mn 0.5 ]O 2 cathodes, attempts have been made to increase the Ni, which is the main redox species (Ni 2+ ↔ Ni 4+ ) in the layered crystal structure, resulting in the Ni‐rich, Co‐free Li[Ni 0.8 Mn 0.2 ]O 2 , and Li[Ni 0.9 Mn 0.1 ]O 2 (denoted as NM90) cathodes that deliver increased discharge capacities and demonstrate improved rate capabilities. [ 13–16 ] However, vigorous reactions between unstable Ni 4+ species and the electrolyte limit the cycle life and thermal stability of the cathodes. [ 15 ] The absence of Co further impairs the stability of the layered crystal structure, as Co 3+ alleviates magnetic frustration during cycling to deter the disordered cation mixing of Li + and Ni 2+ and increases electronic conductivity through CoO 6 octahedra with delocalized electronic states.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrate improved rate capabilities. [13][14][15][16] However, vigorous reactions between unstable Ni 4+ species and the electrolyte limit the cycle life and thermal stability of the cathodes. [15] The absence of Co further impairs the stability of the layered crystal structure, as Co 3+ alleviates magnetic frustration during cycling to deter the disordered cation mixing of Li + and Ni 2+ and increases electronic conductivity through CoO 6 octahedra with delocalized electronic states.…”
mentioning
confidence: 99%